Fiery shapes celestial portents and astrology in Ireland and Wales 650-1650 - Williams, Mark. (Oxford : Oxford University Press, 2010)
This study of the representation of astrology and celestial portents in the medieval and later literature of Ireland and Wales examines the mysterious figure of the druid who was allegedly able to read the future from rainclouds.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 9, 2010).
Keywords: Astrology in literature; Omens in literature; Druids and druidism in literature; Irish literature -- To 1100 -- History and criticism; Irish literature -- Middle Irish, 1100-1550 -- History and criticism; Welsh literature -- To 1550 -- History and criticism